Implementation of the Online Administrative Services Application for Population Management (Pasti Oke) in Garut Regency - Bayu Bastian , Ucep (GoResearch - Research & Publishing House, 2025)
This study employs a qualitative research method to examine the implementation of the PASTI OKE application at the Population and Civil Registration Office of Garut Regency. The objective of this research is to understand how the PASTI OKE application is implemented at the Population and Civil Registration Office of Garut Regency. This study is motivated by the fact that the majority of the public are unaware that population administration services are now available online. The techniques used to collect data in this study include interviews, documentation, and observation. The data analysis process involves steps such as reducing data, presenting data, and finally drawing conclusions. The number of research informants is three people. The results of the study indicate that one of the factors hindering the implementation of the PASTI OKE application is the community, particularly the elderly and residents with limited access to digital technology. To address this, the Population and Civil Registration Office has assigned two staff members to each sub-district to socialize and assist the community in using population services through the PASTI OKE application.